Changes in oral health in patients with Behçet's disease: 10-year follow-up [Behçet hastalarında oral saǧlıǧın deǧişimi: 10 yıllık i̇zlem çalışması] - (:unkn) unknown (Marmara University, 2011)
Objective: The aim of this retrospective study was to evaluate the changes in oral health parameters in patients with Behçet's disease (BD) in a 10-year follow-up study. Patients and Methods: Eighteen BD patients (F/M: 12/6, mean 36.4 ± 9.9 years) followed regularly by clinical, laboratory and oral health examinations for 10 years, were included in the study. Oral health was evaluated by dental and periodontal indices. Patients were given oral hygiene education regularly in each visit. In addition, the number of oral ulcers per month was noted and a disease activity score was calculated. Results: Although the frequency of tooth brushing was higher for the 10-year follow up (median:1.2) than for the baseline (1.0), no significant difference was observed (p=0.06). Also there were no significant differences for the scores of periodontal indices and dental indices at baseline and follow-up (p>0.05). The number of oral ulcers/month was lower at follow-up (median:1) compared to baseline (median:6) (p=0.000). Conclusion: Although painful ulcers affect oral health negatively, dental and periodontal health remained stable in a 10-year follow-up in BD patients with motivation and education for oral hygiene. However, further studies are required to demonstrate whether better oral hygiene effects the course of oral ulcers.
Keywords: Behçet's disease; Oral health; Oral hygiene; Oral ulcer